High-throughput microtiter assay for Hoechst 33342 dye uptake - Seigel, Gail M. (Kluwer Academic Publishers, 2004)
Exclusion of Hoechst 33342 dye is a characteristic common to stem cells, as well as chemotherapy-resistant cancer cells. Normally, these dye-excluding cells can be sorted from enzymatically dissociated tissues with a UV cell sorter/flow cytometer. UV-flow cytometry can be expensive, time-consuming and not readily available to all laboratories. We have developed a simple, high-throughput 96-well microtiter plate assay by which cell populations can be quickly screened for Hoechst dye uptake and exclusion. The method is compatible with green-fluorescent EGFP expressing cells, often used in stem cell biology. Useful applications for this assay will be the rapid screening of clonal stem cell populations and tumor cells for Hoechst dye uptake.